2020
DOI: 10.1186/s12916-020-01705-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effect of school closure during COVID-19 outbreaks in Ontario, Canada

Abstract: Background The province of Ontario, Canada, has instituted indefinite school closures (SC) as well as other social distancing measures to mitigate the impact of the novel coronavirus disease 2019 (COVID-19) pandemic. We sought to evaluate the effect of SC on reducing attack rate and the need for critical care during COVID-19 outbreaks, while considering scenarios with concurrent implementation of self-isolation (SI) of symptomatic cases. Methods We developed an age-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 45 publications
5
48
1
Order By: Relevance
“…This is due in part to our assumption that asymptomatic and 11 symptomatic infections contribute similarly to transmission [26,67,37,36,68], and in part to our model's ability to capture chains of transmission within schools and extending out into the community. Our study echoes several modeling studies in emphasizing the importance of reducing school capacity to impede transmission [61,62,63,64,72]. Taking all this evidence together, those deciding on strategies to safely reopen schools should strongly consider operating at reduced capacity and strictly enforcing face-mask adherence.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…This is due in part to our assumption that asymptomatic and 11 symptomatic infections contribute similarly to transmission [26,67,37,36,68], and in part to our model's ability to capture chains of transmission within schools and extending out into the community. Our study echoes several modeling studies in emphasizing the importance of reducing school capacity to impede transmission [61,62,63,64,72]. Taking all this evidence together, those deciding on strategies to safely reopen schools should strongly consider operating at reduced capacity and strictly enforcing face-mask adherence.…”
supporting
confidence: 71%
“…There is now a growing body of evidence that school closures contributed to mitigating the first wave of the epidemic and could lead to rising case numbers if relaxed [6,62]. Our study adds to this evidence, and suggests an even greater impact of school reopening than several other studies [64,62,61,72,60]. This is due in part to our assumption that asymptomatic and 11 symptomatic infections contribute similarly to transmission [26,67,37,36,68], and in part to our model's ability to capture chains of transmission within schools and extending out into the community.…”
mentioning
confidence: 52%
“…Some have shown that closing schools in U.S. states led to lower case number and infection rates [38]. Others have shown that, in Canada and Australia, school closures may have limited impact on reducing disease spread [39,40]. A review paper systematically examines research on the effectiveness of school closures at containing coronavirus outbreaks and concludes that school closures do not contribute to the control of the pandemic, especially in comparison to policies that broadly restrict the movement of adults [41].…”
Section: Policy Studiesmentioning
confidence: 99%
“…As mentioned earlier, there were two types of outcomes in our results. As can be seen in was a substantial disparity between those who died (9 days, IQR [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]) and those who survived (6 days, IQR [4][5][6][7][8][9][10][11]) in the median LOS. Figure 2.…”
Section: Patient Outcomesmentioning
confidence: 99%